PENGARUH KEPEMIMPINAN ETIS DAN KEADILAN DISTRIBUTIF TERHADAP INTERNAL WHISTLEBLOWING DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL PEMODERASI - Stefani Fierzca Dewi (Jurnal Akuntansi dan Pajak, 2023)
Introduction/Main Objective: This study investigates the role of ethical leadership and distributive justice in encouraging internal whistleblowing behavior. Background: The application of whistleblowing is used as one of the organization's internal controls in detecting fraud. However, most employees who have the intention of doing whistleblowing generally do not wish to report outside the organization (external whistleblowing) and prefer internal whistleblowing. Therefore, further research is needed to determine the factors that will increase a person's intention to conduct internal whistleblowing. Novelty: This study examines the relationship between ethical leadership and distributive justice on internal whistleblowing by examining the moderating role of locus of control. Research Methods: The data collection technique used in this study is an online self-administered survey of employees who work at financial institutions in Indonesia, both banks and non-banks. A total of 140 responses were analyzed through Structural Equation Modeling-Partial Least Square (SEM-PLS) using an analysis tool in the form of SmartPLS version 3.0 to test the research hypothesis. Finding/Results: Analysis of the data collected shows that ethical leadership and distributive justice are positively and significantly related to internal whistleblowing. Furthermore, locus of control moderates the influence of ethical leadership and distributive justice on internal whistleblowing.